Bahasa Indonesia: English - Rahma, Haliatur; Winarto, Winarto; Akbar, Fajar (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2019)
Plant Growth Promoting Rhizobacteria (rhizobacteria)) is a soil bacterium that lives in the root region (rhizosphere), actively colonizes plant roots, can suppress pathogens, and increase plant growth. This study aims to obtain rhizobacterial isolates that have the potential to suppress cob rot disease in planta or in vitro and increase the growth of corn plants. This study used a randomized block design (RBD) for in planta with 15 rhizobacterial treatments, positive control (without F. verticillioides inoculation), and negative controls (F. verticillioides inoculation). Each procedure was repeated three times, and each replication consisted of 3 plants. In vitro testing using a Completely Randomized Design (CRD) with 15 rhizobacterial treatments and one control. Each repeated three times. Data were analyzed using variance analysis, if significantly different, continued with Duncan's New Multiple Range Test (DNMRT) at a 5% level. The results showed that LA2MKB 5.2 isolate was the isolate that had the best ability to suppress the development of F. verticillioides in planta with total effectiveness of 90.14%. LMTSA 5.4 isolate is the isolate that has the highest percentage of inhibition of dual culture in its ability as an antagonist of F. verticillioides in vitro, which is 7.20%.